Studies on fabrication, characterization, and metal extraction using metal chelating nonwoven nanofiber mats of poly(vinyl alcohol) and sodium alginate blends - Rathna, G. V. N.; Birajdar, Mallinath S.; Bhagwani, Manish; Paul, V. L. (Polymer Engineering and Science, 2013)
Poly(vinyl alcohol) and sodium alginate blends with and without the metal chelate, bis(2,4,4-trimethylpentyl)phosphinic acid were prepared in various compositions and fabricated to stable nanofibers and films to evaluate their efficacy for metals adsorption and desorption. Surface morphology of the nanofibers was characterized by scanning electron microscopy. The solution properties and variation in content of sodium alginate in the feed mixture have influenced morphology of nanofibers. However, influence of bis(2,4,4-trimethylpentyl)phosphinic acid was insignificant. The films and nanofibers were characterized using Fourier transform infrared spectroscopy, differential scanning calorimetry, thermo gravimetric analysis, and X-ray diffraction to understand compatibility between polymers, thermal stability, decomposition temperature, and variations in crystallinity. Metal adsorption studies for nanofiber mats comprising bis(2,4,4-trimethylpentyl)phosphinic acid were demonstrated using copper (II), cobalt(II), and nickel(II) salts. The nanofibers adsorbed more copper (363 mg/g) when compared with films (105 mg/g). Nanofiber mats immobilized with bis(2,4,4-trimethylpentyl)phosphinic acid adsorbed copper in greater magnitude (497 mg/g) than nanofiber mats without bis(2,4,4-trimethylpentyl)phosphinic acid (363 mg/g). However, adsorption of cobalt and nickel was very low to be detected. The metal adsorption and desorption studies were also confirmed by energy dispersive X-ray spectroscopy. POLYM. ENG. SCI., 2013. (c) 2012 Society of Plastics Engineers